A Neuroscientist's Guide to the Vole. Issue 6 (25th June 2021) - Kenkel, William M.; Gustison, Morgan L.; Beery, Annaliese K.
Abstract: Prairie voles have emerged as an important rodent model for understanding the neuroscience of social behavior. Prairie voles are well known for their capacity for pair bonding and alloparental care. These behavioral phenomena overlap with human social behavior but are not commonly observed in traditional rodent models. In this article, we highlight the many benefits of using prairie voles in neuroscience research. We begin by describing the advantages of using diverse and non‐traditional study models. We then focus on social behaviors, including pair bonding, alloparental care, and peer interactions, that have brought voles to the forefront of social neuroscience. We describe many additional features of prairie vole biology and behavior that provide researchers with opportunities to address an array of research questions. We also survey neuroethological methods that have been used with prairie voles, from classic to modern techniques. Finally, we conclude with a discussion of other vole species, particularly meadow voles, and their own unique advantages for neuroscience studies. This article provides a foundation for researchers who are new to working with voles, as well as for experienced neuroscientists who want to expand their research scope. © 2021 Wiley Periodicals LLC.